Pulmonary immunity and durable protection induced by the ID93/GLA-SE vaccine candidate against the hyper-virulent Korean Beijing Mycobacterium tuberculosis strain K. Issue 19 (27th April 2016) - Cha, Seung Bin; Kim, Woo Sik; Kim, Jong-Seok; Kim, Hongmin; Kwon, Kee Woong; Han, Seung Jung; Cho, Sang-Nae; Coler, Rhea N.; Reed, Steven G.; Shin, Sung Jae
Abstract: The majority of tuberculosis (TB) vaccine candidates advanced to clinical trials have been evaluated preclinically using laboratory-adapted strains. However, it has been proposed that challenge with clinical isolates in preclinical vaccine testing could provide further and more practical validation. Here, we tested the ID93/GLA-SE TB vaccine candidate against the clinical Mycobacterium tuberculosis (Mtb) strain K (Mtb K) belonging to the Beijing family, the most prevalent Mtb strain in South Korea. Mice immunized with ID93/GLA-SE exhibited a significant reduction in bacteria and reduced lung inflammation against Mtb K when compared to non-immunized controls. In addition, we analyzed the immune responses in the lungs of ID93/GLA-SE-immunized mice, and showed that ID93/GLA-SE was able to elicit sustained Th1-biased immune responses including antigen-specific multifunctional CD4 + T cell co-producing IFN-γ, TNF-α, and IL-2 as well as a high magnitude of IFN-γ response for up to 10 weeks post-challenge. Notably, further investigation of T cell subsets in the lung following challenge showed remarkable generation of CD8 + central memory T cells by ID93/GLA-SE-immunization. Our findings showed that ID93/GLA-SE vaccine confers a high level of robust protection against the hypervirulent Mtb Beijing infection which was characterized by pulmonary Th1-polarized T-cell immune responses. These findings may also provide relevant information for potential utility of this vaccine candidate in East-Asian countries where the Beijing genotype is highly prevalent.